Correlation of Membership in Certain Types of Islamic Mass Organizations on the Tendency to Vote for One of the Presidential Candidates in the 2024 Presidential Election - Susdarwono, Endro Tri; Wiranta, Alma (LAKPESDAM MWCNU Palengaan, 2024)
This research aims to describe the correlation between membership in certain types of Islamic mass organizations and the tendency to vote for one of the presidential candidates in the 2024 presidential election. The Islamic mass organizations in question include Nahdlatul Ulama (NU), Muhammadiyah, Al-Irsyad, and Hizbut Tahrir Indonesia (HTI). The approach in this study uses a type of quantitative descriptive research. The sample of respondents consisted of 130 respondents located in Brebes Regency, Tegal Regency, Tegal City and Pemalang Regency. The criteria used as respondents were respondents who were members of one of the Islamic mass organizations in Indonesia. The sampling technique used random sampling. While the instrument used in this research is a questionnaire. The data analysis technique uses hypothesis testing using the Cramer C correlation method. This research concludes that there is a correlation between membership of certain types of Islamic mass organizations and the tendency to vote for one of the presidential candidates in the 2024 presidential election. The correlation coefficient value is 38.86%, this coefficient is not It is classified as a high correlation, but if there is a correlation, it is clear that there is a correlation between membership in certain types of Islamic mass organizations and the tendency to vote for one of the presidential candidates in the 2024 presidential election. Suggestions for other researchers are that other research be carried out regarding the tendency to vote for one of the presidential candidates. in the 2024 presidential election.